Water Quality Assessment for Batu Pahat River Basin, Malaysia - Sidek L.M.; Jajarmizadeh A.; Mohiyaden H.A.; Noh S.M.; Puad A.H.M.; Shahrir A.M.D. (Springer Science and Business Media Deutschland GmbH, 2023)
River pollution; Rivers; Urban growth; Watersheds; Batu pahat river basin; Malaysia; NQWI; Quality index methods; River basins; Urban development; Urbanization; Water quality assessments; Water quality indexes; Water quality parameters; Water quality